(untitled) (The Review of Diabetic Studies, 2025)
Digital monitoring technologies are transforming hospital safety and risk management by providing continuous, real-time insight into clinical and operational processes. Modern hospitals face diverse threats, including healthcare-associated infections, medication errors, patient deterioration, workplace hazards, and cyberattacks. Traditional monitoring methods—such as manual audits, paper documentation, and retrospective reviews—are often slow, incomplete, and reactive. This scientific paper examines how digital monitoring technologies, including Internet of Things (IoT) sensors, artificial intelligence (AI) analytics, radio-frequency identification (RFID), real-time location systems (RTLS), wearable devices, and electronic incident-reporting platforms, can enhance health security and risk management in hospitals. The paper discusses applications in infection control, patient safety, staff protection, asset tracking, facility management, and cybersecurity. It also explores ethical and legal considerations and outlines future directions for smart hospital ecosystems. A comparative table is provided to summarize the main characteristics, advantages, and limitations of key digital monitoring tools.